Endowment as an Educational Fundraising Tool for Entrepreneurial University: the U.S. Experience versus Ukrainian Reality and Perspectives - Krasulia, Alla (Wydział Studiów Edukacyjnych Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2014)
Educational fundraising could pose significant challenges for Ukrainian universities in times of neoliberal ideology of contemporary educational reforms. The purpose of this paper is to provide an analysis of the best fundraising practices in public US universities in order to implement them in the area of higher education in Ukraine. Examples and data published in a range of educational science journals as well as Ukrainian state laws are analyzed to highlight the purposes, features, and structure of university financial endowments. The article focuses on the “Triple Helix” model as one of the most effective schemes of university development. All things considered it can help Ukrainian universities carry on their social mission, funding various activities relating to education, research, and innovation.
Obdarzenie (kapitał docelowy) jako sposób pozyskiwania funduszy dla przedsiębiorczego uniwersytetu: amerykańskie doświadczenie a ukraińskie realia i perspektywy
Keywords: endowment; educational fundraising; university mission; triple helix; higher education